2016
DOI: 10.1161/strokeaha.115.012321
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Drug Use, Blood Pressure Variability, and Incident Stroke Risk in Older Adults

Abstract: Background and Purpose-The aim was to determine the association between antihypertensive drug class and incident stroke controlling for long-term blood pressure (BP) variability (BPV) in people aged ≥65 years. Methods-The sample included 5951 participants (median age 74 years, 60% women) taking at least 1 drug for hypertension (3727/5951) or with systolic BP >140 mm Hg or diastolic BP >90 mm Hg. Participants were evaluated for incident fatal and nonfatal stroke to 12 years follow-up. BPV was calculated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…24 Blood pressure variability (BPV), a natural characteristic of blood pressure (BP), is the result of complex interactions between extrinsic environmental and behavioral factors and intrinsic cardiovascular regulatory mechanisms (neural central, neural reflex, and humoral influences). BPV is correlated with the risk of stroke, 5 and BPV is especially detrimental to the occurrence of hemorrhagic stroke. However, the clinical implications of markedly elevated BPV in the setting of acute hemorrhagic stroke are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…24 Blood pressure variability (BPV), a natural characteristic of blood pressure (BP), is the result of complex interactions between extrinsic environmental and behavioral factors and intrinsic cardiovascular regulatory mechanisms (neural central, neural reflex, and humoral influences). BPV is correlated with the risk of stroke, 5 and BPV is especially detrimental to the occurrence of hemorrhagic stroke. However, the clinical implications of markedly elevated BPV in the setting of acute hemorrhagic stroke are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Over a median follow-up of 12 years, Schutte et al 24 found that SBP variability did not predict any fatal or nonfatal cardiovascular events, including stroke. In another study, Tully et al 25 also showed that there was no association between SBP variability and the incidence of stroke in people aged ≥65 years. Given these controversial results, we conducted an analysis to explore the relationship between SBP variability and the risk of stroke in a large-scale Chinese general population.…”
Section: Discussionmentioning
confidence: 93%
“…Antihypertensive drugs have been reported to be effective on preventing SIE. (23) Among different classes, Tully et al (24) reported that angiotensin receptor blocker (ARB) and beta-blocker were associated with ischemic stroke. Oppositely, Tziomalos et al (25) reported that ARB was more effective on SIE preventing than any other classes.…”
Section: Discussionmentioning
confidence: 99%